TRANSESTERIFICATION OF BIODIESEL FROM KAPOK SEED OIL (Ceiba pentandra) - Nove Kartika Erliyanti; Afida Kartika Sari; Achmad Chumaidi; Rachmad Ramadhan Yogaswara; Erwan Adi Saputro (Konversi, 2021)
The purpose of this study was to determine the effect of KOH concentration and reaction time on the flash point and pour point of biodiesel from kapok seed oil. The biodiesel transesterification process is carried out in a batch reactor equipped with stirrer. The first step in this research is to reduce the free fatty acid content (esterification process). The second step is transesterification of biodiesel from kapok seed oil. The concentrations of KOH used in this research were 0.5, 1.0, 1.5, and 2.0% by weight of the oil and the reaction time were 0.25, 0.5, 1.0, and 1.5 hours. The operating conditions used in this study were a temperature of 60 oC and a pressure of 4 bar. The results showed that the concentration of KOH and reaction time had a significant effect on the flash point and pour point of biodiesel. The best flash point and pour point were obtained at a concentration of 0.5% KOH and a reaction time of 1.5 hours, which were 163 oC and -8 oC.